AMT (ACHIEVEMENT MOTIVATIONTRAINING) SEBUAH RANCANGAN INTERVENSI UNTUK MENINGKATKAN EFIKASI DIRI PADA MAHASISWA PROGRAM KHUSUS ULAMA IAIN ANTASARI BANJARMASIN (STUDI EKSPERIMEN) - Mulyani, Mulyani; Mubarak, Mubarak; Hairina, Yulia (Jurnal Studia Insania, 2015)
Belief or self efficacy is owned by someone to do an action influences activities and efforts of someone in facing difficulty of finishing of certain assignment. Especially, college students who are in Program Khusus Ulama in IAIN Antasari, they need to have a belief with theirselves to finish the final assignment as a schedule decided. With this reason, to increase the self efficacy this study designed an Achievement Motivation Training (AMT). It is a training oriented to increase motivation to achieve some goals had have decided by individuals based on their ability. The research subject invited to know theirselves more through self evaluation based on other people assessment. Then, deciding some goals wants to reach and deciding a strategy and a target based on their ability achieved from result of self evaluation. Sample of this research was 10 people and to decide experiment participation by random sampling. This training was for college students of Program Khusus Ulama of Tafsir Hadis department in Faculty of Ushuluddin and Humaniora. The conclusion is that Achievement Motivation Training (AMT) has effects to increase self efficacy of ollege students of Program Khusus Ulama. The score of Self Efficacy showed that students? self efficacy proven higher than before they follow the AMT.